INTERDISCIPLINARY APPROACH IN THE TREATMENT OF CONGENITALLY MISSING LATERAL INCISOR - Daniela Anistoroaei; Cătălina Iulia Săveanu; Loredana Golovcencu; Eduard Radu Cernei; Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2019)
In dentistry treatment of difficult cases may be accomplished using an interdisciplinary approach. This article describes the orthodontic treatment in a female patient (12-years old) which was diagnosed with congenitally missing of upper left lateral incisor and Angle's Class III malocclusion. The treatment plan was interdisciplinary using preprosthetic orthodontic treatment for facilitate the surgical, implant and restorative treatment. The treatment were favorable, fulfilled the patient expectation and improving facial esthetics and restoring the functions. This case demonstrates that an interdisciplinary team (orthodontist, dental surgeon, prosthodontist) is required for the successful treatment of the congenitally missing of lateral incisor to create ideal conditions for the insertion of the dental implant.